2023
DOI: 10.3390/f14040761
|View full text |Cite
|
Sign up to set email alerts
|

Landscape Design Intensity and Its Associated Complexity of Forest Landscapes in Relation to Preference and Eye Movements

Abstract: Understanding how people perceive landscapes is essential for the design of forest landscapes. The study investigates how design intensity affects landscape complexity, preference, and eye movements for urban forest settings. Eight groups of twenty-four pictures, representing lawn, path, and waterscape settings in urban forests, with each type of setting having two groups of pictures and one group having four pictures, were selected. The four pictures in each group were classified into slight, low, medium, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The typical value for the FD range of the chorioretinal vasculature in human eyes is 1-2. This number characterizes the amount of space filled by chorioretinal vascular branches or the complexity of vascular branching [ 52 ]. Different thresholding methods result in different amounts of FD as a sample shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The typical value for the FD range of the chorioretinal vasculature in human eyes is 1-2. This number characterizes the amount of space filled by chorioretinal vascular branches or the complexity of vascular branching [ 52 ]. Different thresholding methods result in different amounts of FD as a sample shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Results indicated that the public preferred a scenario with a high proportion of trees, relatively open space, mild and uniform color tones, suitability for movement, and the ability to produce a restorative and peaceful atmosphere. Shen et al combined objective and subjective landscape complexity to investigate the effects of landscape design intensity on preference and eye movement [19]. They suggested that the significant relationship between objective or subjective landscape complexity, or preference and eye movement metrics, was dependent on landscape types.…”
Section: Summary Of Articles Included In the Special Issuementioning
confidence: 99%